The Influence of HMOs on the Efficiency of Primary Health Care Provided in the NHIS in FCT, Abuja - Emmanuel, Emelda Ifeanyi; Sampson, Joseph Maren (NIU Journal of Social Sciences; Vol 6 No 3 (2020): KIU Journal of Social Sciences, Vol. 6 No. 3, September 2020, 2020)
The study focused on the influence of HMOs on the efficiency of primary health care provided in FCT, Abuja. The essence was to investigate how HMOs performance or nonperformance of their duties can impact on the efficiency of primary health care providers and the National Health Insurance Scheme on the overall. The scheme is believed to have a model designed to suit the country. With HMOs as major partners in the scheme, it is believed that the scheme would function better and would facilitate the goal of covering more people within the shortest possible time. Although HMOs activities can be done by NHIS itself, the efficiency of the scheme may be threatened due to the nonchalant attitude of some public sector workers in the discharge of their duties. Usually the results of partnership are greater and more effective the world all over. If HMOs execute their duties to PHCPs properly, this would in turn positively impact the NHIS. From the data analyzed, the findings of this research showed that HMOs had significant impact on the efficiency of primary Health Care Providers at varying degrees. Also, HMOs played significant role in the scheme and had impact on the overall scheme. Keywords: Primary Health Care Providers, Health Maintenance Organization, National Health Insurance Scheme.